Targeting MAGE-C1/CT7 expression increases cell sensitivity to the proteasome inhibitor bortezomib in multiple myeloma cell lines. - Fabricio de Carvalho (Public Library of Science (PLoS), 2011)
The MAGE-C1/CT7 encodes a cancer/testis antigen (CTA), is located on the chromosomal region Xq26-27 and is highly polymorphic in humans. MAGE-C1/CT7 is frequently expressed in multiple myeloma (MM) that may be a potential target for immunotherapy in this still incurable disease. MAGEC1/CT7 expression is restricted to malignant plasma cells and it has been suggested that MAGE-C1/CT7 might play a pathogenic role in MM; however, the exact function this protein in the pathophysiology of MM is not yet understood. Our objectives were (1) to clarify the role of MAGE-C1/CT7 in the control of cellular proliferation and cell cycle in myeloma and (2) to evaluate the impact of silencing MAGE-C1/CT7 on myeloma cells treated with bortezomib. Myeloma cell line SKO-007 was transduced for stable expression of shRNA-MAGE-C1/CT7. Downregulation of MAGE-C1/CT7 was confirmed by real time quantitative PCR and western blot. Functional assays included cell proliferation, cell invasion, cell cycle analysis and apoptosis. Western blot showed a 70-80% decrease in MAGE-C1/CT7 protein expression in inhibited cells (shRNA-MAGE-C1/CT7) when compared with controls. Functional assays did not indicate a difference in cell proliferation and DNA synthesis when inhibited cells were compared with controls. However, we found a decreased percentage of cells in the G2/M phase of the cell cycle among inhibited cells, but not in the controls (p<0.05). When myeloma cells were treated with bortezomib, we observed a 48% reduction of cells in the G2/M phase among inhibited cells while controls showed 13% (empty vector) and 9% (ineffective shRNA) reduction, respectively (p<0.01). Furthermore, inhibited cells treated with bortezomib showed an increased percentage of apoptotic cells (Annexin V+/PI-) in comparison with bortezomib-treated controls (p<0.001). We found that MAGE-C1/CT7 protects SKO-007 cells against bortezomib-induced apoptosis. Therefore, we could speculate that MAGE-C1/CT7 gene therapy could be a strategy for future therapies in MM, in particular in combination with proteasome inhibitors.